THE UTILIZATION OF LANDSAT 8 FOR MAPPING THE SURFACE WATERS TEMPERATURE OF GRUPUK BAY - WEST NUSA TENGGARA: WITH IMPLICATIONS FOR SEAWEEDS CULTIVATION - Bidawi Hasyim; Syarif Budiman; Arlina Ratnasari; Emiyati; Anneke K. S. Manoppo (International Journal of Remote Sensing and Earth Sciences, 2015)
Locating a suitable site is the key to success in cultivating seaweed, as it is becomes one of the coastal and marine prospects for improving the national economy. Numerous factors such as water movement, substratum, depth, salinity, light intensity, surface water temperature, influence the growth of this aquatic plant, and should be considered while choosing a farming area. One of key parameters on studying sea water conditions is surface temperature distribution, as changes on temperature effecting physical, chemical, and biological condition of the sea water. Surface waters temperature is affected by radiation, and sun position, geographic, seasons, overcast, interaction process between air and waters, evaporation level, and wind blowing. It's rarely easy job to measure surface waters temperature, because often, researcher has to deal with strong winds and high waves. The objectives of this research is to do surface waters temperature mapping of Grupuk Bay – West Nusa Tenggara, using thermal infrared channel of Landsat8 data, which is supported by field observation data. Surface temperature measurement is conducted through field survey in conjunction with Landsat 8 orbit. Surface temperature calculation is carried out by using certain method issued by United States Geological Survey (USGS, 2013). Calculation result on Grupuk Bay's water surface temperature shows that it ranges from 28.00 to 30.00oC, while field survey result shows that it ranges from 28.27 to 29.69oC. This research shows that sea surface temperature measurement result based on Landsat8 data has nearly identical range with field survey result.